2013
DOI: 10.1002/hep.26176
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of and risk factors for hepatocellular carcinoma in primary biliary cirrhosis: National data from Japan

Abstract: Primary biliary cirrhosis (PBC) primarily affects females and is rarely complicated by hepatocellular carcinoma (HCC). Although the HCC incidence in PBC patients is low, several characteristics and risk factors associated with its development have been reported. In this study, national data concerning the current status of carcinogenesis in PBC patients in Japan are reviewed. Using data from two national questionnaire surveys, we investigated the clinicopathological findings associated with HCC in PBC patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
50
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 23 publications
10
50
2
1
Order By: Relevance
“…We also found that HCC development is a significant risk factor for survival in patients with PBC. Because the PBC patients had already progressed to an advanced histological stage at the time of HCC diagnosis, these results appear to be reasonable and are consistent with those of a study from Spain and Italy (9) and a recent Japanese report based on a nationwide survey (10). In fact, the six PBC patients with HCC (6/9, 67%) evaluated in the present study died of hepatic failure (Table 2).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We also found that HCC development is a significant risk factor for survival in patients with PBC. Because the PBC patients had already progressed to an advanced histological stage at the time of HCC diagnosis, these results appear to be reasonable and are consistent with those of a study from Spain and Italy (9) and a recent Japanese report based on a nationwide survey (10). In fact, the six PBC patients with HCC (6/9, 67%) evaluated in the present study died of hepatic failure (Table 2).…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, whether the development of HCC affects the overall survival of patients with PBC remains controversial (5,7,9,10). This matter and the identification of risk factors for HCC development are of importance for improving the prognosis of patients with PBC.…”
Section: _ _mentioning
confidence: 99%
“…HCC occurred in less than 5% of patients, but the risk was significantly increased by increased age, male sex, diabetes mellitus, and previous hepatitis B virus infection [46]. In another large cohort in Japan, the HCC incidence was 2.4% (71/2946), and male sex and advanced histological stage in females are independent risk factors for the development of HCC in patients with PBC [45].…”
Section: Causes Of Deathmentioning
confidence: 94%
“…A recent study conducted by [44]. The role of male sex in the development of HCC in PBC has also been found in a representative cohort of Chinese and Japanese patients with a long follow-up [45,46]. A large cohort of 1865 well-defined Chinese patients with PBC were evaluated for the incidence of HCC up to 20 years.…”
Section: Causes Of Deathmentioning
confidence: 99%
“…Over 50% of the annual HCC cases reported worldwide are diagnosed in the Chinese population (3), while hepatitis B virus (HBV) infection is responsible for 80% of all HCC causes in China (4). While a number of studies have revealed that HBV infection is the key pathogenic factor for the development of HCC, male gender and cirrhosis have also been found to be independent risk factors for the occurrence of HCC (5)(6)(7). However, few studies exist on patients presenting all these risk factors.…”
Section: Introductionmentioning
confidence: 99%